2015
DOI: 10.1007/s10753-015-0217-y
|View full text |Cite
|
Sign up to set email alerts
|

FOXO3 rs12212067: T > G Association with Active Tuberculosis in Han Chinese Population

Abstract: It is well known that the human innate immune and adaptive immune response play important role in tuberculosis (TB) infection and progress. Emerging evidence shows that FOXO3 plays an important role in the human immune system. Recent research has shown that the FOXO3 genetic variants are associated malaria infection. In this study, 268 confirmed TB patients, 321 patients with latent tuberculosis infection (LTBI), and 475 TB-free controls were recruited; the single-nucleotide polymorphism (SNP) rs12212067: T > … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…This is in agreement with previous studies that reported an abrogation of FOXO3 expression in active TB patients, compared to healthy controls (30,53). It has been also shown that an SNP affecting FOXO3 expression was associated with active TB in a dominant inheritance mode (54). Taken together, our study presents a strong evidence that FOXO3 constitutes a major signaling hub that is manipulated by mycobacterial species and that disruption of FOXO3 signaling might affect the regulation of anti-M.tb directed immune response.…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with previous studies that reported an abrogation of FOXO3 expression in active TB patients, compared to healthy controls (30,53). It has been also shown that an SNP affecting FOXO3 expression was associated with active TB in a dominant inheritance mode (54). Taken together, our study presents a strong evidence that FOXO3 constitutes a major signaling hub that is manipulated by mycobacterial species and that disruption of FOXO3 signaling might affect the regulation of anti-M.tb directed immune response.…”
Section: Discussionsupporting
confidence: 93%
“…It has been discussed that some SNPs may actually be associated with MTB infection [ 36 , 37 ], some may be associated with active TB [ 38 , 39 ] and other studies suggested some SNPs may have different impacts on the susceptibility to LTBI and PTB [ 32 , 40 , 44 ]. Lu et al found that an immunity-related GTPase family M SNP was associated with active TB and LTBI, but also plays opposite roles in the development of active TB and LTBI [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, however, we did find additional evidence that the genetic contribution to prognosis may be shared between distinct diseases. For example, the FOXO3 haplotype that was associated with a milder course of Crohn's disease, and reduced TNFα production, has also been associated with a milder course of rheumatoid arthritis and with more severe courses of malaria and tuberculosis . Similarly, the IGFBP1 / IGFBP3 locus that was associated with more aggressive Crohn's disease was previously shown to associate with anti‐citrullinated peptide antibodies in rheumatoid arthritis …”
Section: Looking Beyond Disease Susceptibility Variantsmentioning
confidence: 97%